Poetic Realism after the Liberation: Gender, Montmartre and Post-Occupation Memory in Macadam (1946). Issue 1 (1st October 2022) - Nevin, Barry
Although generally overlooked by scholars, Macadam constitutes a key example of how filmmakers in post-war France attempted to lend continuity to 1930s oetic realist praxis. The present analysis suggests that Macadam's aesthetics not only raise profound questions regarding the relationship between France's pre-war and post-war identities, but also bear the creative imprint of the film's artistic director, Jacques Feyder. In order to address each of these concerns, this article proceeds in three key stages. First, it illustrates the extent to which 1930s poetic realist working practices and generic conventions permeated cinema of the Liberation with reference to Feyder. Second, it considers the salience of poetic realist tropes within the film, paying particular attention to framing, setting and characterisation. Third, it discusses how the film's representation of women contradicts the misogynistic tendencies in gender representation that characterised French cinema after the Liberation. This article ultimately aims to demonstrate that Macadam on the one hand, constitutes an extension of poetic realism's visual style and gender politics, and on the other hand, extends Feyder's own history of interrogating retrograde gender paradigms.